A Meta-Analysis for the Efficacy of Hypnotherapy in Alleviating PTSD Symptoms. Issue 1 (2nd January 2016) - Rotaru, Tudor-Ștefan; Rusu, Andrei
Abstract: A systematic review and meta-analysis of the efficacy of hypnotherapy in the treatment of PTSD used literature searches to obtain 47 articles. However, only 6 were experiments testing the efficacy of hypnosis-based treatments. A fixed-effects meta-analysis was applied to postintervention assessment results and 4-week follow-ups. A large effect in favor of hypnosis-based (especially manualized abreactive hypnosis) treatment was found for the studies that reported the posttest results ( d = 1.17). The temporal stability of the effect remains strong, as reflected by the 4-week follow-up assessments ( d = 1.58) and also by long-term evaluations (e.g., 12 months). Hypnosis appears to be effective in alleviating PTSD symptoms.